Dexamethasone Attenuates the Enhanced Rewarding Effects of Cocaine Following Experimental Traumatic Brain Injury - Steven F. Merkel; Allison M. Andrews; Evan M. Lutton; Roshanak Razmpour; Lee Anne Cannella; Servio H. Ramirez (Cell Transplantation, 2017)
Clinical studies have identified traumatic brain injury (TBI) as a risk factor for the development of cocaine dependence. This claim is supported by our recent preclinical studies showing enhancement of the rewarding effects of cocaine in mice sustaining moderate controlled cortical impact (CCI) injury during adolescence. Here we test the efficacy of dexamethasone, an anti-inflammatory corticosteroid, to attenuate augmentation of the behavioral response to cocaine observed in CCI-TBI animals using the conditioned place preference (CPP) assay. These studies were performed in order to determine whether proinflammatory activity in the nucleus accumbens (NAc), a key brain nucleus in the reward pathway, mediates enhanced cocaine-induced CPP in adolescent animals sustaining moderate CCI-TBI. Our data reveal robust glial activation in the NAc following CCI-TBI and a significant increase in the cocaine-induced CPP of untreated CCI-TBI mice. Furthermore, our results show that dexamethasone treatment following CCI-TBI can attenuate the cocaine place preference of injured animals without producing aversion in the CPP assay. Our studies also found that dexamethasone treatment significantly reduced the expression of select immune response genes including Monocyte chemoattractant protein-1 (MCP-1/CCL2) and intercellular adhesion molecule-1 ( ICAM-1 ), returning their expression to control levels, which prompted an investigation of peripheral blood monocytes in dexamethasone-treated animals. Experimental findings showed that no craniectomy/dexamethasone mice had a significant increase, while CCI-TBI/dexamethasone animals had a significant decrease in the percentage of circulating nonclassical patrolling monocytes. These results suggest that a portion of these monocytes may migrate to the brain in response to CCI-TBI, potentially sparing the development of chronic neuroinflammation in regions associated with the reward circuitry such as the NAc. Overall, our findings indicate that anti-inflammatory agents, such as dexamethasone, may be effective in normalizing the rewarding effects of cocaine following CCI-TBI.